Significance of salivary phosphodiesterase level in oral squamous cell carcinoma patients - Chianeh, Yousef Rezaei; Prabhu, Krishnananda; M, Rashmi; Fernandes, Donald J. (International Journal of Research in Medical Sciences, 2017)
Oral cancer, more specifically oral squamous cell carcinoma (OSCC) consider as common cancer that 300,000 people diagnosed per year worldwide. The only effective treatment for OSCC is surgical intervention. Over the past two decades, overall disease condition has not improved although advancement of treatment has considerably increased. The phosphodiesterase (PDEs) are responsible for the hydrolysis of the second messengers with a fundamental role in the transduction of the intracellular signals. In numerous pathological conditions such as cellular differentiation, apoptosis, and tumor invasivity the different PDF activity has been observed that shown role in pathophysiological mechanism. The role of PDEs as an intervention factor for activation of angiogenesis by influencing a tumor growth has been shown. The objective of this study was to estimate and compare salivary PDEs levels in healthy controls and biopsy-proven oral cancer patients before definitive therapy. Study was done in patients age between 25-65 years biopsy proven oral cancer patients and control group. After obtaining prior consent from biopsy-proven oral cancer patients (n=26) (before onset of any definitive treatment) and age- and sex-matched healthy controls (n=29), salivary sample was collected for estimation of the activity of phosphodiesterases (PDEs).